Physicians' beliefs about brain surgery for drug-resistant epilepsy: A global survey. (December 2022) - Asadi-Pooya, Ali A.; Brigo, Francesco; Trinka, Eugen; Lattanzi, Simona; Karakis, Ioannis; Kishk, Nirmeen Adel; Valente, Kette D.; Jusupova, Asel; Turuspekova, Saule T.; Daza-Restrepo, Anilu; Contreras, Guilca; Kutlubaev, Mansur A.; et al.
Highlights: 1410 physicians from 20 countries and different world regions participated. The propensity to discuss brain surgery with patients was higher among men. In comparison to neurologists, psychiatrists were less likely to discuss about it. In comparison to neurologists, neurosurgeons were more likely to discuss about it. Abstract: Purpose: To investigate the opinions of physicians about brain surgery for drug-resistant epilepsy worldwide. Methods: Practicing neurologists, psychiatrists, and neurosurgeons from around the world were invited to participate in an online survey. The survey anonymously collected data about demographics, years in clinical practice, discipline, nation, work setting, and answers to the questions about beliefs and attitudes about brain surgery for drug-resistant epilepsy. Results: In total, 1410 physicians from 20 countries and different world regions participated. The propensity to discuss brain surgery with patients, who have drug-resistant seizures, was higher among men (versus women) [Odds Ratio (OR) 1.67, 95% CI 1.20–2.31; p = 0.002]. In comparison to neurologists, psychiatrists were less likely (OR 0.28, 95% CI 0.17–0.47; p < 0.001) and neurosurgeons were more likely (OR 2.00, 95% CI 1.08–3.72; p = 0.028) to discuss about it. Survey participants working in Africa, Asia, the Middle East, and the Former Union of Soviet Socialist Republics showed a lower propensity to discuss epilepsy surgery with patients. Conclusion: This study showed that on an international level, there is still a knowledge gap concerning epilepsy surgery and much needs to be done to identify and overcome barriers to epilepsy surgery for patients with drug-resistant seizures worldwide.